Error Analyses and the Cognitive or Linguistic Influences on Children’s Spelling: Comparisons Between First- and Second-Language Learners - Harrison, Gina Louise (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2021)
A collection of cognitive, linguistic, and spelling measures were administered to third- grade English L1 and L2 learners. To capture formative assessments of children’s developing mental graphemic representations (MGRs), spelling errors in isolation were subjected to analysis across three metrics: (1) Phonological constrained; (2) Visual- Orthographic; and (3) Correct Letter Sequences. There were no group differences on the cognitive or spelling accuracy measures, but L1 learners achieved higher scores than L2 on linguistic measures of vocabulary and syntactic knowledge. Analyses across the spelling metrics indicated that both L1 and L2 learners drew more heavily on their knowledge of graphophonemic rules and positional constraints in pronunciation for spelling. However, the contribution of underlying cognitive and linguistic resources to spelling differed as a function of scoring system and language group. Across spelling metrics, linguistic predictors (vocabulary and syntactic knowledge) accounted for more variance in L1 than L2 learners. The results are discussed in relation to conceptualization of spelling as an integral link between oral and written language in literacy development.